Methylome-wide Analysis Reveals Epigenetic Marks Associated With Resistance to Tuberculosis in Human Immunodeficiency Virus–Infected Individuals From East Africa. (5th January 2021) - Stein, Catherine M; Benchek, Penelope; Bartlett, Jacquelaine; Igo, Robert P; Sobota, Rafal S; Chervenak, Keith; Mayanja-Kizza, Harriet; von Reyn, C Fordham; Lahey, Timothy; Bush, William S; Boom, W Henry; Scott, William K; et al.
Abstract: Background: Tuberculosis (TB) is the most deadly infectious disease globally and is highly prevalent in the developing world. For individuals infected with both Mycobacterium tuberculosis ( Mtb ) and human immunodeficiency virus (HIV), the risk of active TB is 10% or more annually. Previously, we identified in a genome-wide association study (GWAS) a region on chromosome 5 associated with resistance to TB, which included epigenetic marks that could influence gene regulation. We hypothesized that HIV-infected individuals exposed to Mtb who remain disease free carry epigenetic changes that strongly protect them from active TB. Methods: We conducted a methylome-wide study in HIV-infected, TB-exposed cohorts from Uganda and Tanzania and integrated data from our GWAS. Results: We identified 3 regions of interest that included markers that were differentially methylated between TB cases and controls with latent TB infection: chromosome 1 ( RNF220, P = 4 × 10 –5 ), chromosome 2 (between COPS8 and COL6A3, P = 2.7 × 10 –5 ), and chromosome 5 ( CEP72, P = 1.3 × 10 –5 ). These methylation results co-localized with associated single-nucleotide polymorphisms (SNPs), methylation QTLs, and methylation × SNP interaction effects. These markers were in regions with regulatory markers for cells involved in TB immunity and/or lung. Conclusions: Epigenetic regulation is a potential biologic factor underlying resistance to TB in immunocompromised individuals that can act in conjunction with genetic variants. Abstract : Epigenetic factors are associated with tuberculosis (TB) susceptibility in HIV-infected individuals, and these methylation marks colocalize with genetic variants also associated with TB. This analysis reveals potential epigenetic effects that regulate lung function and TB immunity.